Locking Up Youth: The Impact of Race on Detention Decisions - Wordes, Madeleine (Journal of research in crime and delinquency, 1994)
Prior research has produced inconsistent findings regarding the relationship between race and secure detention of juveniles. Many previous studies were conducted in single jurisdictions, had limited measures of offense seriousness, often did not examine the influence of social factors, and experienced sample selection problems. Using data on felony offenses in five counties, this study examined detention at three stages in the juvenile justice process: police detention, court intake detention, and preliminary hearing detention. Data were collected from case files in police agencies and juvenile courts to reflect actual offense behavior and the youths' family and social situations. Bivariate and logistic regression techniques were used to explore the issue of racial disparity. Findings indicated that African American and Latino youth were more likely to be detained at each decision point, even after controlling for the influence of offense seriousness and social factors